Presbyastasis: A multifactorial cause of balance problems in the elderly - Christine Rogers (South African Family Practice)
Presbyastasis is the result of age-related physiological changes in the three sensory systems and their central connections that contribute to balance. In all likelihood, presbyastasis is a complex condition involving many intertwined systems rather than a lesion within the vestibular system only, thus evaluation and management need to be holistic. Balance problems can have detrimental consequences and are associated with falls, loss of quality of life and psychological sequelae such as anxiety, depression and panic. Healthcare practitioners need increased awareness of the pathophysiology of presbyastasis and its possible impact.